In search of America - Jennings, Peter, 1938-; Brewster, Todd. (New York : Hyperion, 2002)
Anchorman Peter Jennings and television producer Todd Brewster present six stories, set in six different locations, which examine central themes of contemporary American life.
Includes bibliographical references (p. [288]-291) and index.
Keywords: United States -- Civilization; United States -- Civilization -- 1970-; United States -- History